Prevalence, predictors and types of unpleasant and adverse effects of meditation in regular meditators: international cross-sectional study - Luca Pauly; Niklas Bergmann; Inge Hahne; Sarah Pux; Eric Hahn; Thi Minh Tam Ta; Michael Rapp; Kerem Böge (BJPsych Open, 2022)
Background Meditation is commonly implemented in psychological therapies since the ‘third wave’ of cognitive–behavioural therapy has increased the focus on mindfulness-based interventions. Although extensive research literature demonstrates its benefits, little is known about potential adverse effects.